Spartan Spanker. - San Jose State Normal School:::Creator::::::::::::; Taylor, Tank (artist):::Contributor::::::::::::
Cover page of the Spartan Spanker, a magazine created and published by students of the San Jose State Normal School. The cover shows a male college student with a raised paddle ready to spank a female college student who is picking up a flower.